2015
DOI: 10.3386/w21544
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Feasibility of Delaying Social Security: Evidence from Administrative Tax Data

Abstract: The findings and conclusions expressed are solely those of the author(s) and do not represent the views of the U.S. Department of the Treasury, or the NBER. We thank seminar participants at George Mason University's School of Policy, Government, and International Affairs and the Tax Economists Forum for helpful comments. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…We find that, if an individual can afford to self-finance consumption in the early years of retirement (i.e., has a personal discount rate below 7.25 percent), the implied cost of borrowing from future benefits yields a lower present discounted value of total pension benefits. This is similar to work by Slavov (2014a, 2014b), Goda, et al (2015), and Bronshtein, et al (2016), who show 3 Individuals, and their spouses, must make numerous decisions as they near retirement including retirement timing, Social Security claiming, work after retirement, and disposition of wealth from retirement saving plans. Throughout this analysis, we also do not explicitly consider these decisions.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…We find that, if an individual can afford to self-finance consumption in the early years of retirement (i.e., has a personal discount rate below 7.25 percent), the implied cost of borrowing from future benefits yields a lower present discounted value of total pension benefits. This is similar to work by Slavov (2014a, 2014b), Goda, et al (2015), and Bronshtein, et al (2016), who show 3 Individuals, and their spouses, must make numerous decisions as they near retirement including retirement timing, Social Security claiming, work after retirement, and disposition of wealth from retirement saving plans. Throughout this analysis, we also do not explicitly consider these decisions.…”
Section: Introductionsupporting
confidence: 66%
“…The crucial question is how an individual should finance consumption in the early years of retirement and how this impacts future retirement income security. At near-zero real interest rates, liquidating retirement savings (e.g., IRAs) is preferable to early Social Security claiming (Shoven and Slavov, 2014a, 2014band Goda, et al, 2015. In this study, we illustrate that the key is the relative interest rate of borrowing.…”
mentioning
confidence: 90%
“…We note, however, thatGoda, Shoven, Ramnath, and Slavov (2015) found that one-third of Social Security early retirees had financial assets in their Individual Retirement Accounts sufficient to finance at least two additional years of deferral, and about one-quarter could self-finance at least four years of deferral. Other assets were not included in that calculation, so that the likely impact of liquidity constraints is probably far lower.10 As noted above, the survey module is detailed inMaurer, Mitchell, Rogalla, and Schimetschek (2016a).…”
mentioning
confidence: 61%
“…First, individuals may want to stop working and lack liquidity to finance the period between retirement and claiming. Goda et al (2017) show that one-third to two-thirds of individuals have sufficient retirement wealth to finance a two-year gap between retirement and claiming. In addition, many individuals who claim Social Security before full retirement age simultaneously delay withdrawing money from their retirement accounts until they are forced to do so at age 70½, a behavior that is inconsistent with the liquidity explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have documented that individuals who have higher subjective or actual mortality risk tend to claim earlier (e.g., Goda et al 2017;Hurd, Smith, and Zissimopoulos 2004;Glickman and Hermes 2015;Beauchamp and Wagner 2012;Waldron 2002). However, high mortality risk is not likely to explain why most people claim at or before fully retirement age, particularly given that even those with twice the average mortality risk stand to gain from delay (Shoven and Slavov 2014a).…”
Section: Introductionmentioning
confidence: 99%